Results of experimental development of a laparoscopic method for auto transplantation of splenic tissue under a liver capsulе method - Dynnik, Anna G.; Babich, Igor I. (International Journal of Psychosocial Rehabilitation, 2020)
Despite the fact, spleen considers to be an important immunomodulating organ, splenectomy continues to be a primary tactic during extensive spleen injuries. Modern laparoscopic technologies force us to look for new low-invasive splenic autotransplantation methods. Meanwhile, the momentous aspect of such invasion is topographical and anatomical transplantation zone choosing, which allows maintaining the physiological connection between portal blood-flow and neo-splenic tissue. 47 experimental animals were included in exploration with the following steps of the study: experimental modeling laparoscopic splenic autotransplantation, dynamic clinical indicators monitoring of animals, experimental animal removal with further histological evaluation of neo-splenic tissue zone in the liver area. Clinical and histological data were evaluated on 7th, 15th, 30th and 60th days after surgery. Histological examination was provided by hematoxylin-eosin staining, magnification: eyepiece W-PL 10x / 23; A-Rlan 100x / 1.25 lens. Statistical data processing was performed using the program Statistica v.6.0. Clinical indicators normalization in the main group was observed by the 15th day. Absence of clinical blood parameters statistical difference between healthy animals and animals after surgery was observed by the 30th day (Р<0.05). The histological structure of the neo-splenic tissue and spleen of intact rabbits is identical, by the 60th day. Our experiment showed the feasibility of further splenic autotransplantation investigation and implementation of this method in endoscopic treatment of abdominal organs traumatic injuries.